Build your own low-budget, energy-efficient NetTop PC. (PC World Philippines)
The System Build project is to build a basic, power-efficient NetTop PC for students to use and play around with during the summer months, on a low-budget. Pre-set requirements included a low-power, energy-efficient platform, with internet connectivity, atleast 1GB of RAM, an LCD monitor, and a spacious hard drive. It also included a list of suggestions to give some upgrade options.